Causes of maternal mortality at tertiary care hospital - G., Vijayalakshmi; N., Usharani; Khazi, A. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal mortality is a vital index of quality and efficiency of obstetric service, prevailing in a country. Women comprise an important section of any population and during child bearing period, the threat to life is protected by various preventive and therapeutic measures and many a time by surgical intervention. Methods: A thorough analysis of data collected. Information was obtained from case sheets, laboratory investigations. During the present study, total births include live births, still births and deaths due to abortions are also included, since it is ‘one of the important causes of maternal deaths. Results: According to the above table Eclampsia is the main cause of direct death. Out of 25vaginal deliveries 7 cases died due to PPH (26.92%). Conclusions: Maternal Mortality is a global problem every country in the world is facing .We need to target specific interventions for specific population.